Enhanced Visual Attentional Modulation in Patients with Inherited Peripheral Retinal Degeneration in the Absence of Cortical Degeneration. (25th June 2019) - Ferreira, Sónia; Pereira, Andreia Carvalho; Quendera, Bruno; Reis, Aldina; Silva, Eduardo Duarte; Castelo-Branco, Miguel
Abstract : The role of attentional mechanisms in peripheral vision loss remains an outstanding question. Our study was aimed at determining the effect of genetically determined peripheral retinal dystrophy caused by Retinitis Pigmentosa (RP) on visual cortical function and tested the recruitment of attentional mechanisms using functional magnetic resonance imaging (fMRI). We included thirteen patients and twenty-two age- and gender-matched controls. We analyzed cortical responses under attentional demands and passive viewing conditions while presenting a visual stimulus covering the central and paracentral visual field. Brain activity was studied in visual areas V1, V2, and V3 as well as in cortical regions of interest corresponding to the preserved and the damaged visual field. The influence of visual field extent and age of disease onset were also investigated. Cortical thickness of visual areas was also measured. We found that cortical visual responses under attentional demands were increased in patients with larger degeneration of visual field, as demonstrated by significant interaction effects between group and task conditions. Moreover, activation during the task condition was increased for patients in two cortical regions of interest corresponding to the preserved and damaged visual field, specifically in patients with severe visual field loss. These findings were observed in the presence of preserved visual cortical structure. We conclude that RP patients have enhanced visual attention recruitment despite their retinal degeneration, while cortical structure and overall response levels remain intact. The unmasking of feedback signals from higher level visual regions involved in attentional processes may explain the increased cortical responses. These findings are relevant for the design of strategies for treating retinal diseases, based on attentional cuing.